Employment of Exercises with distances less than the distance race for developing copayments endurance speed and effect that on Achieving 400m Running for junior - ali, abass (Journal of Physical Education, 2010)
Ensure that current research objectives are: 1. The preparation of exercises using spaces less than the distance of the race to take the speed of development and the achievement of running 400 meters for juniors. 2. Identify the impact of these exercises by using spaces less than the distance of the race to take the speed of development and the achievement of running 400 meters for juniors. The researcher used the experimental method for its convenience and the nature of research, formed the research sample of (12) runner who trained in Rusafa the field centers and the Center for the People and the Center for Ur district court Scouts and agree to the sample search terms in terms of age, regular communication and training, as it were between the ages between 14 - 16 years, the researcher chose to take a test run speed of 300 meters for measuring the speed of the carrying capacity of the effectiveness of the 400-meter run and test the complete 400-meter run, has hired a researcher extracted the results of statistical treatments. The researcher concluded the following:1.The use of exercises less than a race distance is working to develop sustainability-speed sector to run 400 meters as well as delivery.2. The specificity of training, the quality of the pregnancy test properly trained and certain distances similar to the approach and the actual performance of the race itself and the physical capacity to link Barakd 400 meters and have a positive impact in the development of the performance of the players.The researcher recommended the following: 1. The use of exercise spaces less than a distance race in the development of sustainability and speed of delivery ran 400 meters and the focus is on the distances at least. 2. Research is similar to the middle-distance 800 and 1500 meters and the barriers 400 meters. 3. The use of appropriate duration and intensity in the development of high-speed bearing sector. 4. Researcher recommends that, whenever near the race distance should preferably be made for the development of carrying less than the speed of a race distance for the specificity of the effectiveness of 400 meters.